Monte Carlo simulation of asymmetric flow field flow fractionation - Iliev, O; Nagapetyan, T; Ritter, K (De Gruyter, 2012)
SDEs are used in the description of a variety of industrial processes. While numerous studies on Monte Carlo and multilevel Monte Carlo methods for SDEs used in ﬁnancial engineering (option pricing, calculation of Greeks etc.) are available in the literature, technical applications are not so broadly studied. In this paper we brieﬂy explain the Asymmetric Flow Field Flow Fractionation process for nanoparticle separation, introduce an SDE-based mathematical model, describe a Monte Carlo procedure for its solution, and end by presenting some numerical results.